Disintermediation: Post war reality priorities - Jeremy Cripps (University American College Skopje, 2022)
24 February 2022 marked the end of 78 years of Pax Europaea (Santos, 2022). The international community's path for peace loving nations based on a pledge "never to wage a war again" (Abe, 2013) was decimated. Too many political leaders failed the test for making "the permanence of peace" (Wilson, 1917) an international structure. Peace came under stress and once more we face that reality of war. The immediate impact offers a cornucopia of sanctions undertaken in our world of fake news (Poole, 2019), political unreality (Freeden, 2019), 'strategic deterrence'(Freedman, 2020), and a significant absence of strategic autonomy (Shapira, 2020). The post war realities that we now face come in the context of * post pandemic adjustment, * rising commodity prices, * soaring inflation, * a rush back to geopolitical boundaries, * and war continuing, with no apparent expiration date, in Europe. The purpose of this paper is first to identify the disintermediation of our past peace economy - the already visible system breakdowns and the new realities which accompany and must follow the Ukrainian crisis.
Keywords: 330